Nitrogen fertilizers capsulation with chicken manure suspension in the fluidized bed device - Острога, Руслан Олексійович; Юхименко, Микола Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
Despite the widespread use of nitrogen fertilizers in the cultivation of crops, they have an increased solubility of nutrients, which leads to disruption of the biological rhythm of plant growth and fertilizer overuse. In the paper, it is proposed to cover mineral granules with organic coating in the form of chicken manure. A fluidized bed device should be considered as the most efficient device for mineral granules capsulation. To study this process, the experimental device is proposed and the method of carrying out experiments is developed. Temperature conditions of urea granules capsulation by the chicken manure suspension are established experimentally and the optimal operating mode of the process is determined. The mathematical description of the granule size distribution during capsulation, and the results of analytical calculations and their comparison with the experimental data, is given. This allows predicting the change of the average diameter of granules during capsulation in the fluidized bed.